Conducive TLE Laboratory Environment and Learning Process Skills of the Students in Cluster 4 Schools in Davao City - Ventura, Jeandy I. (Yayasan Sembilan Pemuda Indonesia, 2024)
Fundamentally, a conducive TLE laboratory environment was expected to improve the learning process skills of the students. In this study, the researcher selected 200 junior high school students in Cluster 4 Public Secondary Schools in Davao City as the respondents. Stratified random sampling technique was utilized in the selection of the respondents. A non-experimental quantitative research design using a descriptive-correlational method was employed. The data collected were subjected to the following statistical tools: Mean, Pearson Product Moment Correlation, and multiple linear regression analysis. Findings revealed that the conducive TLE laboratory environment and the learning process skills of the students were described as extensive. Further, correlation analysis demonstrated that there was a significant relationship between a conducive TLE laboratory environment and the learning process skills of the students. Evidently, regression analysis proved that a conducive TLE laboratory environment in terms of open-endedness, rule clarity, and material environment were significant predictors of the learning process skills of the students. In other words, a conducive TLE laboratory environment influenced the learning process skills of the students in Cluster 4 Public Secondary Schools in Davao City.